Zalora Earth Edit: a corporate strategy for sustainable fashion products - Susi Hartanto (Institut Seni Indonesia Yogyakarta, 2022)
As of 2020, Zalora Indonesia campaigned earth friendly products under Earth Edit category. There are 5 Earth Edit Zalora criterias: 1) Earth friendly materials, 2) Earth friendly processes, 3) Fair production processes, 4) Animal friendly, and 5) Community involvement. Each supplier (brand) who wishes to be tagged as earth friendly brands need to go through layers of verification and need to provide certifications as proof. This article is expected to provide a reference for fashion product suppliers in earth friendly area, to be aware of industry standards applied in trusted fashion e-commerce platform in Indonesia.